A method for preparing modified cigarette butt activated carbon microspheres and its application in ammonia adsorption

Modified cigarette buttic carbon microspheres prepared through steps such as water thermal reactions and thermal solution and activation solve the problem of poor effects of existing cigarette butter activated charcoal in adsorption ammonia, and realize high -efficiency ammonia adsorption and stable regenerative cycle performance.

CN116651400BActive Publication Date: 2025-01-24XIANGTAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310785490.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-24
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The existing cigarette butt activated carbon has irregular morphology and structure, relatively single and unstable properties, resulting in poorer effect in adsorption of ammonia.

Method used

Steps are used to react to the ball through water thermal reactions, thermal carbonization activation, and metal chloride modification, etc., to prepare the activated carbon gallery of the cigarette buttic cigarette butt, forming a spherical microsphere of the medium structure, which is suitable for the adsorption of ammonia.

Benefits of technology

The prepared modified cigarette butter activated carbon macro ball has a good ammonia adsorption effect. The ammonia adsorption capacity is as high as 6.0mmol/g ~ 8.0mmol/g, and it has a stable recycled cycle performance. It is suitable for purifying ammonia and wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116651400B_ABST
    Figure CN116651400B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing modified cigarette butt activated carbon microspheres and their application in the adsorption of ammonia. First, a hydrothermal reaction is carried out in the presence of phosphoric acid to obtain a solid primary spheroidized carbon matrix, and then a spherical activated carbon crude product is obtained by pyrolysis and carbonization activation, and then a metal salt is impregnated to obtain modified cigarette butt activated carbon microspheres. The obtained product has a mesoporous structure and a spherical morphology. The diameter of the microspheres is 1 to 30 microns, and the pore size on the microspheres is mainly distributed in the range of 2 to 30 nanometers. The obtained product of the present invention is used for adsorbing ammonia, and the adsorption capacity is as high as 6.0mmol / g to 8.0mmol / g. It can provide an effective, feasible and convenient way to improve the quality of discharged wastewater containing ammonia nitrogen or the quality of waste gas containing ammonia, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of biochar, and in particular to a preparation method of modified cigarette butt activated carbon microspheres and the application of the microspheres in adsorbing ammonia. Background Art

[0002] NH3 and NH 4+ It is the nitrogen-containing species that has the most serious impact on the environment. The increase in the content of nitrogen compounds in water bodies will lead to eutrophication and affect the quality of drinking water. Ammonia and NO discharged into the atmosphere X Ammonium nitrate or ammonium sulfate salts produced by reacting with SO2 are important factors in the formation of haze. NH3 in the atmosphere is highly irritating and can damage the human respiratory tract, eyes, etc. With the growth of population and the increase of human activities, global ammonia emissions have increased dramatically. At the same time, ammonia, as an important fertilizer and industrial raw material, has large-scale applications in the fields of pharmaceuticals, agriculture, and chemicals, and can even partially replace fossil fuels as a low-carbon energy source. Therefore, there is a strong practical demand for the purification of ammonia-containing waste gas and wastewater, and the separation and storage of ammonia, and efficient adsorption materials and technologies have received widespread attention.

[0003] According to statistics, the world consumes a huge amount of cigarettes every year, with as many as 4.95 trillion cigarette butts discarded in the environment. Cigarette butts are difficult to degrade in the natural environment, and trace heavy metals in cigarette butts will leach into the soil and water with rainwater, which not only pollutes the natural environment, but also poses a health threat to humans and organisms in the ecosystem. Therefore, making discarded cigarette butts into activated carbon adsorption materials for purifying pollutants in the environment can achieve waste treatment and is welcomed.

[0004] Chinese invention CN109173994A provides a method for preparing biochar by high-temperature carbonization modification of waste cigarette butts and the application of biochar. The preparation method includes the steps of hydrothermal carbonization, high-temperature pyrolysis activation and acid treatment. The obtained biochar is used as an adsorbent to remove bisphenol A (BPA) in water under different pH conditions, and has obvious selectivity. Chinese invention patent CN111003709B discloses a method for preparing activated carbon using waste cigarette butts and the obtained activated carbon. The method includes the steps of pyrolysis pre-carbonization, activation and pyrolysis carbonization of waste cigarette butts. By optimizing the pre-carbonization conditions, the fiber bundles and tar in the cigarette butts are pre-carbonized, thereby obtaining a better specific surface area, mesoporosity and yield of activated carbon.

[0005] The above-mentioned technical solution of making cigarette butts into activated carbon adsorption materials has indeed achieved a good improvement in certain performances, but the obtained activated carbon is more suitable for adsorbing and purifying organic matter and heavy metals in water bodies. The morphology and structure of the obtained activated carbon are irregular, and it is difficult to further modify it to obtain uniform active sites. The properties are relatively simple and unstable, and good adsorption effects cannot be achieved in the adsorption of ammonia. Summary of the invention

[0006] In view of the technical problems that existing cigarette butt activated carbon has irregular morphology and structure, relatively simple and unstable properties, and poor ammonia adsorption effect, the present invention provides a method for preparing modified cigarette butt activated carbon microspheres and its application in ammonia adsorption.

[0007] The method for preparing modified cigarette butt activated carbon microspheres provided by the present invention comprises the following steps:

[0008] (1) Hydrothermal reaction to form balls: waste cigarette butts, water and / or phosphoric acid solution are placed in a reactor and stirred to obtain a hydrothermal carbon suspension by hydrothermal reaction. The temperature of the hydrothermal reaction is 200° C. to 300° C., and the time is 0.5 h to 3 h. Solid-liquid separation is performed to obtain a solid primary spheroidized carbon matrix.

[0009] (2) Pyrolysis carbonization activation: the primary spheroidized carbon matrix obtained in step (1) is directly dried or evenly mixed with a phosphoric acid solution and then dried, and then pyrolyzed at 500° C. to 800° C. for 0.5 h to 2 h under a protective atmosphere, and then cooled to obtain a crude spherical activated carbon product;

[0010] (3) Metal chloride modification: The crude spherical activated carbon obtained in step (2) is washed and dried, and then placed in a metal chloride solution for modification. After drying, modified cigarette butt activated carbon microspheres are obtained.

[0011] Furthermore, in step (1), the discarded cigarette butts are cigarette butts with residual tobacco removed, preferably cigarette butts with outer wrapping paper removed.

[0012] Furthermore, in step (1), a catalyst is preferably added to the hydrothermal reaction, the catalyst being glucose and / or cellulose, and the amount of the catalyst used being 0.1 to 5% of the mass of the cigarette butt.

[0013] Furthermore, in step (1), the amount of waste cigarette butts and water in the system is 1g: (5-20ml), the water in the system includes water directly added and / or water in the phosphoric acid solution; the temperature of the hydrothermal reaction is 200°C to 300°C, preferably 225-248°C or 250-270°C; and the time is 0.5h to 3h.

[0014] Furthermore, in step (1), the liquid phase obtained by solid-liquid separation is transferred to the next batch of hydrothermal reaction, thereby achieving full utilization of materials including the catalyst.

[0015] Furthermore, in step (2), the pyrolysis temperature is 580-720° C. and the time is 1-1.5 h.

[0016] Furthermore, a phosphoric acid solution is added in at least one of step (1) and step (2), and the total amount of phosphoric acid is 0.5 to 5 times the mass of the discarded cigarette butts. The addition of phosphoric acid solution in step (1) can promote the hydrothermal reaction to a certain extent, and at the same time can prepare for the subsequent activation. Therefore, adding phosphoric acid first in step (1) is a better choice. More preferably, 50% to 100% of the total amount of phosphoric acid is added in step (1), that is, all or part of the phosphoric acid required for activation can be directly added in step (1). When the amount added in step (1) is insufficient, the remaining amount is added in step (2).

[0017] Furthermore, in step (3), the metal chloride is selected from one or more of magnesium chloride, manganese chloride, ferrous chloride, zinc chloride and nickel chloride, the mass fraction of the metal chloride solution is 5% to 30%, and the amount of the metal chloride is 20% to 200% of the quality of the crude spherical activated carbon.

[0018] Furthermore, in step (3), the modification is carried out under stirring and / or ultrasonic conditions, the stirring speed is 250 to 500 r / min, and the ultrasonic period is 20 to 40 min.

[0019] The modified cigarette butt activated carbon microspheres obtained by the above preparation method have a mesoporous structure, the diameter of the microspheres is 1 to 30 microns, and the pore sizes on the microspheres are mainly distributed in the range of 2 to 30 nanometers.

[0020] The modified cigarette butt activated carbon microspheres obtained by the above preparation method are used to adsorb ammonia, which can remove ammonia nitrogen in wastewater or ammonia in ammonia-containing waste gas, and can achieve good adsorption effect, especially the adsorption effect of ammonia in ammonia-containing waste gas is more significant.

[0021] The beneficial effects of the present invention are:

[0022] The present invention uses environmentally polluting discarded cigarette butts as raw materials to prepare mesoporous modified cigarette butt activated carbon microspheres. The preparation process has a stable yield and low production cost. The obtained product also has the advantages of large specific surface area, uniform active ingredient loading, good ammonia adsorption effect, easy regeneration and recycling, etc., thus realizing the resource utilization of discarded cigarette butts.

[0023] The present invention first forms a ball by hydrothermal carbonization, then performs high-temperature pyrolysis activation, and then performs metal salt impregnation to obtain modified cigarette butt activated carbon microspheres, which have a mesoporous structure and a spherical morphology. The diameter of the microspheres is 1 to 30 microns, and the pore size on the microspheres is mainly distributed in the range of 2 to 30 nanometers. The chloride modification process itself is not original to the present invention. However, after obtaining the crude spherical activated carbon, the present invention significantly amplifies the application effect of the obtained product in ammonia adsorption by chloride modification. Chloride modification, especially modification of chlorides such as nickel chloride, can significantly improve the ammonia adsorption effect of the obtained product. In addition, the present invention can not only promote the occurrence of hydrothermal reaction, strengthen the effect of hydrothermal reaction, and better ensure the acquisition of spherical morphology by adding a catalyst and part of the phosphoric acid or all of the phosphoric acid required for activation during the hydrothermal process, but also can further improve the effect of ammonia adsorption of the obtained product, so that the obtained product is more suitable for ammonia adsorption, and the ammonia adsorption capacity is as high as 6.0mmol / g to 8.0mmol / g, which can provide an effective and feasible convenient way to improve the quality of discharged ammonia-nitrogen-containing wastewater or ammonia-containing waste gas, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the process flow of the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the SFC obtained in Comparative Example 1. It can be seen from the image that the carbon matrix spheroidized in one step by the hydrothermal reaction has a preliminary spherical morphology.

[0026] Figure 3 This is a scanning electron microscope image of SFC-20% obtained in Example 1.

[0027] Figure 4 This is a diagram showing the effect of ammonia adsorption in Example 6.

[0028] Figure 5 This is a diagram showing the effect of ammonia adsorption in Example 7.

[0029] Figure 6 This is a diagram showing the effect of ammonia adsorption in Example 8.

[0030] Figure 7 This is a diagram showing the effect of ammonia adsorption in Example 9.

[0031] Figure 8 This is a diagram showing the effect of ammonia adsorption in Example 10.

[0032] Fig. 9 This is a diagram showing the effect of sample regeneration in Example 11.

[0033] Fig.10 This is a scanning electron microscope image of the irregular modified activated carbon sample SFC-D2. It can be seen from the image that SFC-D2 has an irregular morphology. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto.

[0035] Example 1

[0036] A method for preparing modified cigarette butt activated carbon microspheres is carried out according to the following steps:

[0037] (1) removing the outer wrapping paper of the discarded cigarette butts, washing and drying them, and placing them in a hydrothermal autoclave, adding water, catalyst glucose and phosphoric acid solution into the hydrothermal autoclave according to the volume ratio of the discarded cigarette butts to water of 1 g:10 ml, wherein the mass of the catalyst glucose and phosphoric acid is 1% and 50% of the mass of the discarded cigarette butts, respectively, and carbonizing them at 240°C for 2 h by a hydrothermal method, and obtaining a solid by solid-liquid separation, i.e., a primary spheroidized carbon matrix;

[0038] (2) the primary spheroidized carbon matrix prepared in step (1) and a phosphoric acid solution having a mass content of 50% of that of the waste gas cigarette butts are uniformly mixed and dried, and then pyrolyzed at 600° C. for 1 h under nitrogen protection, and then cooled to room temperature in the furnace under protective gas protection to obtain a crude spherical activated carbon product;

[0039] (3) The crude spherical activated carbon obtained in step (2) is washed and then impregnated with a nickel chloride solution with a mass fraction of 20% (also known as mass concentration), and ultrasonically vibrated for 30 minutes to make the nickel chloride precipitate evenly distributed in the crude spherical activated carbon, followed by drying to obtain modified cigarette butt activated carbon microspheres. The obtained sample is recorded as SFC-20%.

[0040] Example 2

[0041] The rest is the same as Example 1, except that the mass fraction of the nickel chloride solution in step (3) is 5%, and the obtained modified cigarette butt activated carbon microspheres are recorded as SFC-5%.

[0042] Example 3

[0043] The rest is the same as Example 1, except that the mass fraction of the nickel chloride solution in step (3) is 10%, and the obtained modified cigarette butt activated carbon microspheres are recorded as SFC-10%.

[0044] Example 4

[0045] The rest is the same as Example 1, except that the mass fraction of the nickel chloride solution in step (3) is 15%, and the obtained modified cigarette butt activated carbon microspheres are recorded as SFC-15%.

[0046] Example 5

[0047] The rest is the same as Example 1, except that the mass fraction of the nickel chloride solution in step (3) is 30%, and the obtained modified cigarette butt activated carbon microspheres are recorded as SFC-30%.

[0048] The modified activated carbon microspheres prepared in Examples 1 to 5 were characterized respectively. Table 1 shows the characterization data and equilibrium adsorption capacity of the five modified activated carbon microspheres. As shown in the data, as the mass concentration of the nickel chloride solution increases from 5% to 30%, the specific surface area of ​​the sample decreases. The pore sizes of the five modified activated carbon microspheres are distributed in the range of 2 to 20 nm, with a peak value of about 3.7, while the molecular size of ammonia is 0.3 nm, which can be smoothly adsorbed in the pores through adsorption.

[0049] Table 1 shows the test data of each sample

[0050]

[0051]

[0052] Example 6

[0053] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The modified cigarette butt activated carbon microspheres prepared in Examples 1 to 5 were subjected to ammonia adsorption tests. The adsorption conditions were an ammonia concentration of 400ppm, an adsorption temperature of 30°C, and a total gas velocity of 0.8L / min. An ammonia detector was used to record the breakthrough time, and data was recorded every 30s after the breakthrough. The test was conducted twice in parallel and the average value was taken. Figure 4 As shown, curve 1 is SFC-20%, curve 2 is SFC-5%, curve 3 is SFC-10%, curve 4 is SFC-15%, and curve 5 is SFC-30%. As the impregnation modification concentration increases from 5% to 20%, the breakthrough time is also extended to 87min, and the maximum equilibrium adsorption capacity (ammonia adsorption saturation capacity) reaches 6.15mmol / g, and the performance of adsorbing ammonia is significantly improved.

[0054] Example 7

[0055] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The sample SFC-20% showing the highest equilibrium adsorption capacity in Example 6 was placed under conditions of different ammonia concentrations for ammonia adsorption tests. Other adsorption conditions were the same as in Example 6, and the ammonia concentrations were adjusted to 200ppm, 300ppm, 400ppm, and 500ppm. Figure 5As shown, curve 6 is 200ppm, curve 7 is 300ppm, curve 8 is 400ppm, and curve 9 is 500ppm. As the NH3 concentration increases from 200ppm to 500ppm, the adsorption rate (i.e., slope) of the test value gradually increases. At the same time, the NH3 adsorption capacity calculated according to the curve increases from 3.87mmol / g to 6.78mmol / g, indicating that the material has strong adaptability to changes in ammonia concentration load.

[0056] Example 8

[0057] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The sample SFC-20% showing the highest equilibrium adsorption capacity in Example 6 was placed under different adsorption temperatures for ammonia adsorption test. Other adsorption conditions were the same as in Example 6, and the adsorption temperatures were adjusted to 30°C, 50°C, 70°C, and 90°C. Figure 6 As shown, curve 10 is 30°C, curve 11 is 50°C, curve 12 is 70°C, and curve 13 is 90°C. At the adsorption temperature of 50°C, the equilibrium adsorption capacity is as high as 7.83mmol / g. When the adsorption temperature rises from 30°C to 50°C, the equilibrium capacity increases by 25%, and the breakthrough time and saturation time shift to the right. When the temperature rises to 90°C, the breakthrough time and saturation time decrease rapidly by 40%. It can be seen that when the temperature rises from 70°C to 90°C, the breakthrough time and saturation time decrease slightly, only 3%.

[0058] Example 9

[0059] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The sample SFC-20% showing the highest equilibrium adsorption capacity in Example 6 was placed under different adsorption temperatures for ammonia adsorption tests. Other adsorption conditions were the same as in Example 6, and the total gas velocity was adjusted to 0.4 L / min, 0.6 L / min, 0.8 L / min, and 1.0 L / min. Figure 7 As shown, curve 14 is 0.4L / min, curve 15 is 0.6L / min, curve 16 is 0.8L / min, and curve 17 is 1.0L / min. As the total gas velocity increases from 0.4L / min to 1.0L / min, the test value adsorption rate gradually increases, and the corresponding equilibrium adsorption capacity increases from 3.44mmol / g to 6.12mmol / g, indicating that the material is also highly adaptable to changes in gas load.

[0060] Example 10

[0061] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The sample SFC-20% showing the highest equilibrium adsorption capacity in Example 6 was placed under different adsorption temperatures for ammonia adsorption test. The other adsorption conditions were the same as in Example 6, and the water vapor content was adjusted to 5%, 15%, 30%, and 60%. Figure 8 As shown, curve 18 is 5%, curve 19 is 15%, curve 20 is 30%, and curve 21 is 60%. It can be found that the water vapor content has a great influence on the sample's adsorption of ammonia. The change in the breakthrough curve shows that under high water vapor content conditions such as 60%, the breakthrough time and saturation time are increased by 30% relative to the water vapor content of 5%. This experiment shows that moisture is conducive to the adsorption or absorption of ammonia on the material, so using this material to treat ammonia nitrogen in wastewater will also have a good effect.

[0062] Embodiment 11

[0063] Modified cigarette butt activated carbon microspheres are used to remove ammonia from ammonia-containing waste gas: The sample SFC-20% showing the highest equilibrium adsorption capacity in Example 6 was regenerated. The regeneration temperature was adjusted to 90°C, 110°C, 130°C, and 150°C. Fig. 9 As shown, curve 22 is 90°C, curve 23 is 110°C, curve 24 is 130°C, and curve 25 is 150°C. By comparison, it can be seen that the desorption amount is the highest when the sample is regenerated at 130°C. After 5 adsorption-regeneration cycle tests, the sample adsorption capacity only decreased by 19%, indicating that the reuse performance is relatively stable and the operating cost can be significantly reduced.

[0064] Example 12

[0065] The rest is the same as Example 3, except that the nickel chloride solution in step (3) is replaced by magnesium chloride solution.

[0066] According to the method of Example 6, ammonia adsorption tests were carried out on the products obtained in Example 3 and Example 12, respectively. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 3 was 3.97 mmol / g, and the ammonia adsorption saturation capacity of the product obtained in Example 12 was 2.38 mmol / g.

[0067] Example 13

[0068] The rest is the same as Example 3, except that the nickel chloride solution in step (3) is replaced by manganese chloride solution.

[0069] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 13 was 2.36 mmol / g.

[0070] Embodiment 14

[0071] The rest is the same as Example 3, except that the nickel chloride solution in step (3) is replaced by ferrous chloride solution.

[0072] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 14 was 3.33 mmol / g.

[0073] Embodiment 15

[0074] The rest is the same as Example 3, except that the nickel chloride solution in step (3) is replaced by zinc chloride solution.

[0075] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 15 was 2.35 mmol / g.

[0076] The ammonia adsorption saturation capacity of the product obtained without impregnation modification is less than 2.11 mmol / g, from which it can be known that the above-mentioned metal chlorides can improve the adsorption performance after modification.

[0077] Example 16

[0078] The rest is the same as Example 1, except that the phosphoric acid solution is all added in step (1).

[0079] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 16 was 8.04 mmol / g.

[0080] Embodiment 17

[0081] The rest is the same as Example 1, except that the phosphoric acid solution is all added in step (2).

[0082] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity of the product obtained in Example 17 was 6.02 mmol / g.

[0083] By comparing the experimental data of Example 16 and Example 17, it can be seen that the addition of the activator phosphoric acid in step (1) of the hydrothermal reaction can show a significantly better ammonia adsorption effect. It is a more conventional operation to add phosphoric acid as an activator when activation is required. The present invention can make the final product obtain a better ammonia adsorption effect by adding the activator phosphoric acid in advance during the hydrothermal reaction.

[0084] Embodiment 18

[0085] Modified cigarette butt activated carbon microspheres are used to remove ammonia nitrogen from wastewater: The modified cigarette butt activated carbon microspheres prepared in Examples 1 to 3 were subjected to batch adsorption tests. Weigh 0.2g of modified cigarette butt activated carbon microspheres into 100mg / L-1000mg / L simulated ammonia nitrogen wastewater prepared with 50mL of ammonium sulfate, and react at a stirring rate of 200 rpm at 20°C for 24h (until the concentration is basically unchanged). After filtering the water sample, the ammonia nitrogen concentration in the filtrate was determined by Nessler's reagent spectrophotometry to obtain the adsorption equilibrium concentration under the corresponding conditions, and the isothermal adsorption curves of the three activated carbon samples were obtained respectively. Then, according to the Langmuir model fitting, the maximum adsorption capacity of activated carbon SFC-5%, SFC-10%, and SFC-20% for ammonia nitrogen was calculated to be 4.87mmol / L, 6.08mmol / g, and 8.32mmol / g, respectively, indicating that the performance of adsorbing ammonia nitrogen in water is good.

[0086] Comparative Example 1

[0087] The rest is the same as Example 1, except that the impregnation modification in step (3) is not performed, and the obtained product is recorded as SFC.

[0088] An ammonia adsorption test was carried out according to the method of Example 6. The experimental results showed that the ammonia adsorption saturation capacity was 2.11 mmol / g.

[0089] It can be seen from Example 6 that under the same conditions, the ammonia adsorption saturation capacity of the product obtained by impregnation with nickel chloride is 6.15 mmol / g. Therefore, in the application of modified cigarette butt activated carbon microspheres to remove ammonia from ammonia-containing waste gas, nickel chloride modification improves the adsorption performance significantly, with an improvement of up to 191%. The data show that the modification of chlorides, especially nickel chloride, is particularly suitable for the application of removing ammonia, and the improvement effect is extremely significant.

[0090] Comparative Example 2

[0091] Remove the outer wrapping paper of the discarded cigarette butts, put them into a hydrothermal kettle, add water according to the volume ratio of the discarded cigarette butts to water of 1g:6ml, heat to 200℃ and perform hydrothermal reaction for about 50min, and separate the solid and liquid to obtain an amorphous solid carbon matrix; perform phosphoric acid activation and carbonization treatment under the same conditions as step (2) of Example 1 to obtain an irregular biochar crude product SFC-D1. Perform impregnation modification on the crude product under the same conditions as step (3) of Example 1 to obtain an irregular modified activated carbon sample SFC-D2. The electron microscope scanning image of SFC-D2 is shown in FIG. Fig.10 As shown by Fig.10 It can be seen that SFC-D2 has an irregular morphology.

[0092] According to the method of Example 6, the ammonia adsorption test was carried out. The experimental results showed that the ammonia adsorption saturation capacity of samples SFC-D1 and SFC-D2 was 0.80mmol / g and 3.20mmol / g. After desorption and regeneration at 130°C and then reused for adsorption, the adsorption capacity of sample SFD2 decreased by about 34% after 5 adsorption-regeneration cycles, indicating that the reuse performance of irregular activated carbon samples is not very stable, while the modified cigarette butt activated carbon microspheres with regular morphology obtained by the present invention have good reuse performance or stability (as shown in the results of Example 11). It can be seen from Example 1 and Comparative Example 1 that under the same conditions, the saturation capacity of the unmodified activated carbon microsphere sample SFC is 2.11mmol / g, which is significantly higher than the ammonia adsorption saturation capacity of the irregular morphology product SFC-D1, and the potential for further modification to improve adsorption performance and reuse stability is greater.

Claims

1. A method for preparing modified cigarette butt activated carbon microspheres, characterized in that: The steps include: (1) Hydrothermal reaction to form balls: waste cigarette butts, water and phosphoric acid solution are placed in a reactor and stirred to obtain a hydrothermal carbon suspension. A catalyst is added to the hydrothermal reaction. The catalyst is glucose and / or cellulose. The amount of the catalyst is 0.1-5% of the mass of the cigarette butts. The temperature of the hydrothermal reaction is 200°C-300°C, the time is 0.5h-3h, and the solid-liquid separation is performed to obtain a solid primary spheroidized carbon matrix. (2) Pyrolysis carbonization activation: the primary spheroidized carbon matrix obtained in step (1) is directly dried or evenly mixed with a phosphoric acid solution and then dried, and then pyrolyzed at 500°C to 800°C for 0.5h to 2h under a protective atmosphere, and then cooled to obtain a crude spherical activated carbon product; (3) Metal chloride modification: The crude spherical activated carbon obtained in step (2) is washed and then placed in a metal chloride solution for modification. The metal chloride is one or more of magnesium chloride, manganese chloride, ferrous chloride, zinc chloride and nickel chloride. The mass fraction of the metal chloride solution is 5% to 30%. The amount of metal chloride used is 20% to 200% of the quality of the crude spherical activated carbon. After drying, modified cigarette butt activated carbon microspheres are obtained.

2. The method for preparing modified cigarette butt activated carbon microspheres according to claim 1, characterized in that: In step (1), the discarded cigarette butts are cigarette butts with residual tobacco removed.

3. The method for preparing modified cigarette butt activated carbon microspheres according to claim 1, characterized in that: In step (1), the amount of waste cigarette butts and water in the system is 1g: (5-20ml); the temperature of the hydrothermal reaction is 225°C-248°C or 250°C-270°C.

4. The method for preparing modified cigarette butt activated carbon microspheres according to claim 1, characterized in that: In step (1), the liquid phase obtained by solid-liquid separation is transferred to the next batch of hydrothermal reaction, thereby achieving full utilization of materials including the catalyst.

5. The method for preparing modified cigarette butt activated carbon microspheres according to claim 1, characterized in that: In step (2), the pyrolysis temperature is 580-720°C and the time is 1-1.5 hours; in step (3), the modification is carried out under stirring and / or ultrasonic conditions, the stirring speed is 250-500 r / min, and the ultrasonic time is 10-60 min.

6. The method for preparing modified cigarette butt activated carbon microspheres according to claim 1, characterized in that: The total amount of phosphoric acid used is 0.5 to 5 times the mass of discarded cigarette butts.

7. The modified cigarette butt activated carbon microspheres obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The modified cigarette butt activated carbon microspheres have a mesoporous structure, a diameter of 1 to 30 micrometers, and a pore size distribution of 2 to 30 nanometers.

8. The use of modified cigarette butt activated carbon microspheres in adsorbing ammonia as claimed in claim 7, characterized in that: The ammonia is ammonia nitrogen in wastewater or ammonia gas in ammonia-containing waste gas.

Citation Information

Patent Citations

  • Method for preparing biochar by high temperature carbonized modified waste cigarette butt and application of biochar

    CN109173994A

  • A method for preparing activated carbon from waste cigarette butts, the resulting activated carbon, and its applications.

    CN111003709B

  • Preparation method of charcoal ammonia adsorbent

    CN111821950A